SECESSION OF TERRITORIAL FORMATION - Стогова, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The problem of separation of territorial formation from the state (secession) is examined. Modern approaches to the decision of secession are analysed. Principle of territorial integrity of the state and peoples right to self-determination are investigated. An author compares mechanisms of secession, provided of the legislation of Canada, Belgium, USSR. The author made the conclusion about a right on secession as guarantees of saving of territorial integrity of the state.